On certainty / edited by G.E.M. Anscombe and G.H.Von Wright ; Translated by Denis Paul and G.E.M. Anscombe - "Wittgenestein, Ludwig" (Oxford, 1979)
The first part was written in twenty loose sheets of lined foolscap, undated. These Wittgenstein left in his room in G.E.M. Anscombe's house in Oxford, where he lived from April 1950 to February 1951.